A unified theory of collective action and social change - Medina Sierra, Luis Fernando, 1968- (Analytical perspectives on politics., 2007)
The notion that groups form and act in ways that respond to objective, external costs and benefits has long been the key to accounting for social change processes driven by collective action. Yet this same notion seems to fall apart when we try to explain how collectivities emerge out of the choices of individuals. This book overcomes that dilemma by offering an analysis of collective action that, while rooted in individual decision making, also brings out the way in which objective costs and benefits can impede or foster social coordination. The resulting approach enables us to address the causes and consequences of collective action with the help of the tools of modern economic theory. To illustrate this, the book applies the tools it develops to the study of specific collective action problems such as clientelism, focusing on its connections with economic development and political redistribution; and wage bargaining, showing its economic determinants and its relevance for the political economy of the welfare state. "Medina's study is a great step forward in the analytics of collective action. He shows the inadequacies of currently standard models and shows that straightforward revisions reconcile rational-choice and structural viewpoints. It will influence all future work."--Kenneth Arrow, Stanford University "Olson, Schelling, and now Medina. A Unified Theory deepens our understanding of collective action and contributes to the foundations of our field. A major work."--Robert H. Bates, Harvard University "Medina thinks that the main problem of social action is not whether or not to cooperate but how to do it. To this end he has produced an imaginative approach to analyzing strategic coordination problems that produces plausible predictions in a range of circumstances."--John Ferejohn, Stanford University Luis Fernando Medina is Associate Professor in the Department of Politics at the University of Virginia